TAXONOMIC STUDIES ON ORTHOPTERA FAUNA OF UDANTI WILDLIFE SANCTUARY, GARIYABAND, CHIHATTISGARH, INDIA - GUPTA, SUNIL KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
The study presents taxonomic account of 50 species pertaining to 45 genera under 8 families of Orthoptera from Udanti Wildlife Sanctuary, Gariyaband, Chhattisgarh, India.